Kebutuhan Buku Ajar Pembelajaran Membaca Bermuatan Cerita Rakyat Melayu Riau - Elva Triwanda Siregar; Asnawi Asnawi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Teaching materials are an important aspect in the world of education because teaching materials are a means to support the learning process. The method used in this research is descriptive method. In this study, the data collection techniques used were interview techniques, documentation techniques, and questionnaire techniques. Based on qualitative analysis, the research data is compiled based on the steps contained in the content analysis method. These steps are carried out through three stages of the water model, namely data reduction, data presentation, and verification. The data in this study can be obtained from the analysis of the needs of reading learning textbooks which contain the text of Riau Malay folklore obtained from the results of the student needs questionnaire. Based on the description and analysis of the data, it can be concluded that the need for reading learning textbooks contains the text of Riau Malay folklore) presentation feasibility aspect, (d) language feasibility aspect, and (e) Riau Malay folklore text content aspect.